2022
DOI: 10.47268/ballrev.v3i1.929
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Opportunities and Challenges in Dispute Resolution of Fintech Sharia Business Through LAPS

Abstract: This research was conducted to outline the opportunities and challenges of resolving fintech business disputes through the Alternative Dispute Resolution Institute (LAPS) in Indonesia. The research method used in this research is a legal reasearch approach and qualitative approach that is to review primary and secondary data sources related to regulations on business dispute resolution in Indonesia. The results show that fintech plays a role in encouraging the economic development of the community, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Based on the results of the study, it was stated that there was a positive relationship between personality and pro-environmental behavior in students of SMAN 27 Jakarta. Likewise research was found that there was an effect of guided discovery learning with argument mapping on the critical thinking skills of high school students (Nurhayati, Nurjamil, et al, 2022;Ristanto et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Based on the results of the study, it was stated that there was a positive relationship between personality and pro-environmental behavior in students of SMAN 27 Jakarta. Likewise research was found that there was an effect of guided discovery learning with argument mapping on the critical thinking skills of high school students (Nurhayati, Nurjamil, et al, 2022;Ristanto et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Starting in 2021, the establishment of LAPS SJK abolished all six LAPS, with the addition of the fintech sector, as mentioned under their OJK Regulation no. 61 of 2020 (Abubakar & Handayani, 2021;Nurhayati et al, 2022).…”
Section: The Development Of Laps Sjk In Indonesiamentioning
confidence: 99%
“…It is believed that this integration may significantly impact Malaysian society. As in Indonesia, the Alternative Institution for Dispute Resolution in the Financial Services Sector (LAPS SJK) was established in 2021 as the new entity, replacing the six previous financial institutions to govern many areas of financial scope and customers, including fintech (Nurhayati et al, 2022). In Australia, the Australian Financial Complaints Authority (AFCA) institution was introduced in 2017 to avoid overlapping jurisdiction and inconsistent outcomes for the complainant (Noone & Ojelabi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Family support can be an encouragement for family members so attention to appraisal support or rewards must still be maintained and increased. However, so that the assessment or appreciation support can be more optimal, in its application it is more focused on the family, it motivates me to always be patient and steadfast in dealing with problems, the family gives positive praise or appreciation when there is progress in my work, and the family fully supports the actions take (Kunskaja, 2019;Nurhayati et al, 2022). In work, business opportunities, the existence of family support will increase the willingness of the community to achieve their business or business.…”
Section: The Effect Of Family Support On Business Opportunitiesmentioning
confidence: 99%